A. James Hudspeth (1945–2025): A pioneer in the biology and physics of hearing - Pascal Martin; Jonathon Howard (Proceedings of the National Academy of Sciences, 2026)
A. James (Jim) Hudspeth, who devoted five decades to studying how hair cells—the mechanoreceptor cells of the inner ear—mediate the senses of hearing and balance, passed away on August 16, 2025, at his home in New York City. He was 79. Among his many achievements, Jim elucidated how mechanical vibrations of the hair cell’s antenna—the hair bundle—evoke electrical signals that convey information to the brain and discovered that hair bundles not only serve as sensors but also act as active mechanical amplifiers of their own inputs. Through the groundbreaking nature and the breadth of his findings, the elegance of his experimental approaches and publications, his transformative mentorship of generations of students and postdoctoral fellows, and his ability to work and communicate across disciplinary boundaries, he has secured his legacy as one of the premier neuroscientists of our time.